A large pedigree study confirmed the CGG repeat expansion of RILPL1 Is associated with oculopharyngodistal myopathy - Xinzhuang Yang; Dingding Zhang; Si Shen; Pidong Li; Mengjie Li; Jingwen Niu; Dongrui Ma; Dan Xu; Shuangjie Li; Xueyu Guo; Zhen Wang; Yanhuan Zhao; et al. (BMC, 2023)
Abstract Background Oculopharyngodistal myopathy (OPDM) is an autosomal dominant adult-onset degenerative muscle disorder characterized by ptosis, ophthalmoplegia and weakness of the facial, pharyngeal and limb muscles. Trinucleotide repeat expansions in non-coding regions of LRP12, G1PC1, NOTCH2NLC and RILPL1 were reported to be the etiologies for OPDM. Results In this study, we performed long-read whole-genome sequencing in a large five-generation family of 156 individuals, including 21 patients diagnosed with typical OPDM. We identified CGG repeat expansions in 5'UTR of RILPL1 gene in all patients we tested while no CGG expansion in unaffected family members. Repeat-primed PCR and fluorescence amplicon length analysis PCR were further confirmed the segregation of CGG expansions in other family members and 1000 normal Chinese controls. Methylation analysis indicated that methylation levels of the RILPL1 gene were unaltered in OPDM patients, which was consistent with previous studies. Our findings provide evidence that RILPL1 is associated OPDM in this large pedigree. Conclusions Our results identified RILPL1 is the associated the disease in this large pedigree.